2014
DOI: 10.1080/15388220.2014.912956
|View full text |Cite
|
Sign up to set email alerts
|

Olweus Bullying Prevention Program: Components Implemented by Elementary Classroom and Specialist Teachers

Abstract: We investigated implementation fidelity of programmatic activities of the Olweus Bullying Prevention Program (OBPP) among 2,022 teachers, 88.5% female, from 88 elementary schools located in Pennsylvania. Results indicated that the majority of respondents had attended the school kick-off event, posted the rules in the classroom, and explained the rules to students. Receiving booster sessions and activities involving parental involvement were the least likely elements to have been performed. Logistic regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 54 publications
(128 reference statements)
0
8
0
Order By: Relevance
“…(2 studies) In one study, the selfefficacy of teachers was not connected to the time that the teachers actually spent on the implementation of the KiVa anti-bullying program (originally developed by Salmivalli and colleagues for schools in Finland) or the amount of lessons they gave on it (Swift 2016/Swift et al 2017). In the second study that addressed this topic, Cecil and Molnar-Main (2015) found that teachers with higher self-efficacy beliefs implemented the Olweus Bullying Prevention Program more extensively. When interpreting these results, it must be noted that each of these studies assessed a different form of self-efficacy.…”
Section: Connections Between Teachers' Self-efficacy and Bullying-rel...mentioning
confidence: 99%
“…(2 studies) In one study, the selfefficacy of teachers was not connected to the time that the teachers actually spent on the implementation of the KiVa anti-bullying program (originally developed by Salmivalli and colleagues for schools in Finland) or the amount of lessons they gave on it (Swift 2016/Swift et al 2017). In the second study that addressed this topic, Cecil and Molnar-Main (2015) found that teachers with higher self-efficacy beliefs implemented the Olweus Bullying Prevention Program more extensively. When interpreting these results, it must be noted that each of these studies assessed a different form of self-efficacy.…”
Section: Connections Between Teachers' Self-efficacy and Bullying-rel...mentioning
confidence: 99%
“…Findings from the current research also indicate that while the bullying field as a tique (Bhaskar, 2016, p. 3), the strong idea of the whole-school approach (Farrington & Ttofi, 2009;Rigby & Slee, 2008;Ttofi & Farrington, 2011;Vreeman & Carroll, 2007) Farrington & Ttofi, 2009;Rigby & Slee, 2008;Ttofi & Farrington, 2011;Vreeman & Carroll, 2007) can be seen as perpetuating a narrow understanding of curriculum that is counterproductive to bullying prevention. Several of the programmes investigated in this study (Bonell et al, 2018;Cecil & Molnar-Main, 2015;Cross et al, 2018;Haataja et al, 2014) subscribe to this approach, and typically include anti-bullying policies, student curriculum, staff training, and engagement with parents and community.…”
Section: Discussionmentioning
confidence: 99%
“…In the programme category, understanding of curriculum can be described using three main themes. First, several studies emphasise teacher training for and student engagement with lessons on bullying (Cecil & Molnar-Main, 2015;Domino, 2013;Haataja et al, 2014;Low et al, 2014). It also discusses how teacher fidelity (Bonell et al, 2018;Cecil & Molnar-Main, 2015;Renshaw & Jimerson, 2012) and the scope of programming affect staff support.…”
Section: Themes In the Programme Categorymentioning
confidence: 99%
See 2 more Smart Citations